2008
DOI: 10.1007/s11199-008-9574-4
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Ways to Motivation Gains in Groups

Abstract: Recent studies have demonstrated motivation gains of low performing group members even beyond the level of an individual work baseline (e.g., Weber and Hertel, Journal of Personality and Social Psychology, 93:973-993, 2007). We expected that the underlying mechanisms of these motivation gains, i.e., social indispensability and social competition, are moderated by individuals' gender. Moreover, these gender effects were assumed to be moderated by partner anonymity. Predictions were tested with mostly undergrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 67 publications
3
27
0
Order By: Relevance
“…Weber et al . () demonstrate that men are particularly prone to such competitive behavior. Male auditors may therefore feel compelled to match or beat their female teammates' higher citation rates.…”
Section: Hypothesesmentioning
confidence: 98%
See 1 more Smart Citation
“…Weber et al . () demonstrate that men are particularly prone to such competitive behavior. Male auditors may therefore feel compelled to match or beat their female teammates' higher citation rates.…”
Section: Hypothesesmentioning
confidence: 98%
“…Furthermore, men on mixed teams may work harder if they sense they are being outperformed by women. Studies have shown that lower performing team members often compare themselves to better performers and that this motivates them to improve their performance to equal or exceed that of the stronger performers (Lount and Phillips, ; Weber, Wittchen, and Hertel, ). Weber et al .…”
Section: Hypothesesmentioning
confidence: 99%
“…The cultural background of a person could provide similar moderating influences. For instance, indispensability effects have been found to be stronger among participants from a collectivistic culture (China) compared with participants from an individualistic culture (Germany; Hertel, Weber, & Yang, 2009, unpublished data). And members of Korean groups appear to take the age of fellow group members into account, working harder when their more capable partners were younger versus older, unlike members of American groups who do not seem to feel different levels of responsibility for a younger versus an older partner (Seok, 2007).…”
Section: Boundary Conditions and Moderating Variablesmentioning
confidence: 99%
“…Other potential moderators of the indispensability mechanism are related to the value a person places on the outcomes of high effort. One well documented person‐related moderator in this category is gender (e.g., Weber, Wittchen, & Hertel, 2009). Consistent with the assumption that women place higher values on helping and assuming responsibility for others than men do, social indispensability effects have been shown to be stronger for women than for men in same‐gender groups (Kerr et al., 2007a; Weber & Hertel, 2007).…”
Section: Boundary Conditions and Moderating Variablesmentioning
confidence: 99%
See 1 more Smart Citation